Percentage of follicle number by size over the antral follicle count and its association with subsequent reproductive performance in beef cattle - Shiori Saito KOHIGASHI; Mizuho UEMATSU; Go KITAHARA; Takeshi OSAWA (The Journal of Reproduction and Development)
This study aimed to clarify the association between the percentage of follicle number by size over antral follicle count (AFC) and subsequent reproductive performance. A total of 306 Japanese Black cattle underwent timed artificial insemination (TAI) 41–62 days postpartum; the AFC and numbers of small, medium, and large follicles were recorded 10 days before TAI. The cross-sectional and blood flow areas of the dominant follicle (DF) on the day of TAI and the corpus luteum (CL) six days after TAI were recorded. The total number of follicles ≥ 2 mm was defined as the AFC, and the percentages of follicle number by each size defined as small (S-AFC%; 2–2.9 mm), medium (M-AFC%; 3–8.4 mm), and large (L-AFC%; ≥ 8.5 mm) follicles. The AFC and S-, M-, and L-AFC% were further grouped into low, medium, and high tertiles, and the subsequent reproductive performance compared among the groups. Plasma anti-Müllerian hormone (AMH) levels were quantified on the day of AFC measurement. No differences were observed in reproductive performance between the AFC and L-AFC% groups. The high-S-AFC% group showed a 20.6% lower conception rate, 0.58 more AI numbers, and 21.9 longer days open than those of the low-S-AFC% group (P < 0.05). The low-M-AFC% group showed an 18.0% lower conception rate after TAI and 0.54 more AI numbers than those of the high-M-AFC% group (P < 0.05). DF and CL parameters did not differ among the AFC, S-, M-, and L-AFC% groups. Plasma AMH levels in the low-AFC group were the lowest in the tertile. In conclusion, the percentage of follicles by size could be used to estimate subsequent reproductive performance.